KORELASI ANTARA MINAT DAN KEAKTIFAN SISWA DENGAN HASIL BELAJAR PADA PEMBELAJARAN TEMATIK KELAS III - Andry Hariyani; Tahmid Sabri; Hery Kresnadi (Universitas Tanjungpura, 2022)
This study aims to describe the correlation between student interest and activity with learning outcomes in thematic learning in class III SDN 16 Pontianak City. The method used is a descriptive method with a quantitative approach. The population and sample in this study were all students of class IIIA, amounting to 22 students. Data collection techniques in this study are direct observation techniques, indirect observations and documentary studies. The data collection instruments used were questionnaires and documentation of daily test scores of subthemes 1,2, and 3 themes 2. The results showed that interest in learning in class IIIA SDN 16 Pontianak City was 87.06% in the